Computational study of ignition behavior and hotspot dynamics of a potential class of aluminized explosives. (24th October 2018) - Roy, Ushasi; Kim, Seokpum; Miller, Christopher; Horie, Yasuyuki; Zhou, Min
Abstract: The ignition behavior and hotspot dynamics of a potential class of aluminized energetic materials are studied computationally. The materials consist of HMX (octahydro-1, 3, 5, 7-tetranitro-1, 3, 5, 7-tetrazocine) grains embedded in an aluminum matrix and, henceforth referred to as metal–matrix explosives (MMXs). For the analysis, two different MMXs, the soft MMX with a matrix of 1100 Al alloy and the hard MMX with a matrix of 7075 T651 Al alloy are considered. The thermo-mechanical response of the MMXs are computationally analyzed by subjecting them to monotonic impact loading using a Lagrangian cohesive finite element framework, with their ignition behavior analyzed through characterization of hotspots. For comparison, a polymer-bonded explosive (PBX) consisting of HMX and Estane is also analyzed under the same conditions. The results show that the MMXs have significantly lower propensity for ignition and higher structural integrity than the PBX over the loading velocity range of 200–500 m s −1 .